Social Network Support and Entrepreneurial Intention among University Students in China’s Border Regions: A Parallel Resource-Cognition Mediation Model - zeyan, zhu; Wu, shengyan (Sripatum Review of Humanities and Social Sciences, 2026)
This study examines how social network support shapes entrepreneurial intention among university students in China’s border regions. Drawing on social network theory, social capital theory, and social cognitive theory, it proposes a parallel mediation model in which social capital represents a resource-acquisition mechanism and entrepreneurial self-efficacy represents a cognition-building mechanism. Data were collected through a stratified questionnaire survey administered via the Wenjuanxing WeChat Mini Program between October and December 2025. After excluding low-quality responses, 9,546 valid cases were retained. Reliability, convergent validity, discriminant validity, common method bias, structural paths, bootstrap mediation, competing models, and measurement invariance were assessed using SPSS and AMOS. Structural equation modeling showed that social network support positively predicted social capital, entrepreneurial self-efficacy, and entrepreneurial intention. Both social capital and entrepreneurial self-efficacy significantly mediated this relationship. Competing-model comparison indicated that the parallel mediation model had lower AIC and BIC values than direct-effect, single-mediator, and serial-mediation alternatives. The findings should be interpreted as evidence from a border-region higher education context rather than as evidence of ethnic-group heterogeneity.